Production of phloretin by multi-module carbon flux rewiring in Saccharomyces cerevisiae - Yi Wu; Jiali Gu; Hongye Li; Lin Wang; Qixiao Zhai; Wei Zhao; Rujin Yang; Xiaomei Lyu (Bioresource Technology, 2026)

Microbial diversity and technological characterization of lactic acid bacteria in traditional fermented yak dairy products from Huangnan Prefecture, Qinghai, China - Hongbo Li; Geng Long; Jiali Zhu; Lin Yang; Hongjuan Li; Jinghua Yu (International Dairy Journal, 2026)

A dual-mode self-verification strategy based on the bimetallic ion amplification effect: Enabling highly sensitive detection of the chemotherapy-induced cardiac toxicity biomarkers IL-6 and MPO - Haiying He; Bolu Sun; Jiali Kang; Mian Chen; Chenyu Qin; Xiangdong Wang; Yuxin Dong; Jiaru Fu; Yaru Zhang; Yuqiong Wu; Huajie Li; Lin Yang; et al. (Analytica Chimica Acta, 2026)

Co-occurring Spirogyra sp. and enrofloxacin stressors interact to alter macrophyte interactions: evidence from a freshwater mesocosm experiment - Yuqing Tian; Cheng Lin; Xu Zhang; Hui Yang; Hongzhi Mao; Heyin Wang; Jiali Chen; Donghai Zhang; Jiangtao Hu; Xusheng Gong; Junyan Wu; Yuying Li; et al. (Aquatic Sciences, 2026)

Nanoconfined iron-based catalysts activate peroxymonosulfate via electron transfer and radical pathways for efficient bisphenol A removal - Mingyu Sun; Qingqing Hao; Jingxingyu Wu; Chenye Fu; Long Lin; Guochun Lv; Shihuai Deng; Xiaohui Lu; Jiali Peng (Journal of Hazardous Materials, 2026)

Water-soluble monostearin-derived carbon dots with enhanced antibacterial capacity for food preservations - Jingbo Sun; Liushunhao Chen; Hongchen Li; Xiaobo Liu; Ling Lin; Lei Meng; Tuanhui Chen; Qian Wen; Dong Xu; Jiali Ren (Food Control, 2026)

From copper imbalance to immunometabolic remodeling: cuproptosis-related vulnerability and therapeutic hypotheses in autoimmune diseases - Yang Shao; Rui feng Zhang; Zhonghe Wang; Jiali Gan; Xi juan Jiang; Lin Yang; Zhi jie Song (Inflammation Research, 2026)

A Novel Long-range Excitatory Neural Circuit from the Magnocellular Red Nucleus to Spinal Dorsal Horn Facilitates Neuropathic Pain-like Behaviors in Male Mice - Jiali Shi; Yinfeng Yuan; Yuhao Luo; Yue Guo; Jiashu Lian; Lin Lin; Danni Chen; Qian Wang; Xiumin Xue; Zhichao Chen; Yongjie Wang; Zhihui Huang (Neuroscience Bulletin, 2026)
Neuropathic pain arises from a primary lesion or disease affecting the somatosensory system; however, the brain circuitry underlying the regulation of neuropathic pain remains unclear. The red nucleus (RN) is a critical brain region involved in regulating muscle tension, coordinating movement, and facilitating sensorimotor integration. While some evidence has shown that RN regulates pain, its specific role in neuropathic pain and associated neural circuits remains elusive. In this study, we found that CaMKIIα-positive neurons in the magnocellular red nucleus (RMC CaMKIIα ) were activated following common peroneal nerve (CPN) ligation-induced chronic neuropathic pain in adult male mice. Interestingly, chemogenetic and optogenetic inhibition of these RMC CaMKIIα neurons alleviated the thermal hyperalgesia and mechanical allodynia in the neuropathic pain model mice, whereas activation of these neurons sufficiently induced the mechanical allodynia and thermal hyperalgesia in naïve mice. Trans-synaptic viral tracing studies further revealed that long-range CaMKIIα + neuron projections from RMC to the dorsal horn (DH) facilitated the neuropathic pain-like behaviors following CPN ligation. DH neurons received direct innervation from RMC CaMKIIα neurons, and inhibition of RMC CaMKIIα -DH CaMKIIα circuits alleviated the neuropathic pain in the ligated mice. Taken together, these results identify a novel long-range excitatory neural circuit from RMC to DH that facilitates the neuropathic pain-like behaviors in adult male mice, providing a new target for neuropathic pain treatment.

Vernalization-responsive intronless genes in faba bean and the development of KASP markers - Xiaocen Liu; Jinyang Liu; Jiali Huang; Shuoqian Zhao; Shengqi Chen; Yun Lin; Qiang Yan; Jingbin Chen; Chenchen Xue; Ranran Wu; Yonghai Sun; Yuhua He; et al. (Plant Cell Reports, 2026)

Dynamic ecosystems of tumor drug resistance mechanisms: from molecular heterogeneity to systemic interventions - Qiaohong Bao; Hang Chen; Jiali Wu; Yahui Wang; Xinmei Chen; Zhizhe Lin; Youfa Xu; Jianming Chen (Apoptosis, 2026)

Hetero-folded hBN/graphene with ultrahigh thermal conduction and electrical insulation for reliable thermal management - Han Zhao; Pengyu Zhang; Jingran Guo; Dizhou Liu; Shixuan Dang; Duola Wang; Hongxuan Yu; Jiali Chen; Chuanyun Song; Yuanpeng Deng; Yingde Zhao; Cong Li; et al. (Chemical Engineering Journal, 2026)

A framework for identifying discriminative model, key factors, and precipitation blocking threshold on triggering drought propagation in the Xijiang River Basin (XRB) - Shinan Zhang; Qingxia Lin; Wenjuan Chang; Zhiyong Wu; Tao Peng; Jiali Guo; Xinzhi Wang (Climate Dynamics, 2026)

Enhancing urban bird corridor identification by integrating three-dimensional factors: A validation with citizen science data - Yaling Huang; Ziru Chen; Yankai Huang; Tongyan Li; Chengyu Ran; Ying Lin; Yinghong Ding; Deng Pan; Yuxiang Lan; Jiali Jin; Zhipeng Zhu; Weicong Fu (Urban Forestry & Urban Greening, 2026)

Assessment of dynamic drought risk and transition characteristics by combining an indicator-based approach and Markov chain model - Bin Huang; Tao Peng; Tianyi Fan; Vijay P. Singh; Xiaohua Dong; Qingxia Lin; Wenjuan Chang; Ji Liu; Yan Huang; Jiali Guo; Yinghai Li; Dan Yu (Natural Hazards, 2026)

Nanofibrous core/nanoporous sheath structured ultra–flexible ceramic aerogels for thermal superinsulation - Dizhou Liu; Cong Li; Han Zhao; Hongxuan Yu; Jingran Guo; Shixuan Dang; Duola Wang; Chuanyun Song; Yingde Zhao; Zhengli Yan; Yuanpeng Deng; Jiali Chen; et al. (Science Bulletin, 2026)

Residential greenness, air pollution, and incident age-related macular degeneration: A prospective cohort study - Jiali Wang; Yinyan Gao; Yijuan Lin; Irene X.Y. Wu; Fang Xiao (Journal of Environmental Sciences, 2026)

Dynamic magnetic field enhances aerobic composting humification: Biotic and abiotic mechanisms - Ruizhi Xing; Jiali Wang; Ziyi Fu; Xiaoyan Chen; Zhouwen Yang; Yunrui Xu; Jianhui Huang; Jian Lü; Hao Lin; Zhi Chen; Shungui Zhou (Chemical Engineering Journal, 2026)

Corrigendum to “Evaluation of bacteriostatic and antioxidant screening of secondary metabolites of endophytic fungi in Lanzhou lily” [Bioresour. Technol. Rep. 32 (2025) 102380] - Xinlan Wang; Bolu Sun; Ying Lv; Miao Zhou; Xuanxiu Da; Jiali Kang; Haiying He; Chenyu Qin; Quhuan Ma; Hongxia Shi; Lin Yang; Xiaofeng Shi (Bioresource Technology Reports, 2025)

Evaluation of bacteriostatic and antioxidant screening of secondary metabolites of endophytic fungi in Lanzhou lily - Xinlan Wang; Bolu Sun; Ying Lv; Miao Zhou; Xuanxiu Da; Jiali Kang; Haiying He; Chenyu Qin; Quhuan Ma; Hongxia Shi; Lin Yang; Xiaofeng Shi (Bioresource Technology Reports, 2025)

Dual-ion charge storage mechanism in polypyrrole cathodes for zinc-ion hybrid capacitors - Jiali Zhang; Tao Xue; Yongbiao Mu; Hongjie Li; Chao Yang; Limin Zang; Lin Zeng (Chemical Engineering Journal, 2025)

Natural product-based nanotechnological formulations for colorectal cancer treatment - Lanfang Wu; Jiali Wu; Xinyu Wang; Youfa Xu; Zhizhe Lin; Jianming Chen; Xin Wu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Screening of biocontrol agents against lily bulb rot caused by F. oxysporum and research on their fermentation process - Bolu Sun; Xinlan Wang; Ying Lv; Xuanxiu Da; Miao Zhou; Jiali Kang; Haiying He; Chenyu Qin; Xiangdong Wang; Lin Yang; Quhuan Ma; Hongxia Shi; et al. (Bioresource Technology Reports, 2025)

Red mud amendments reduce cadmium mobility in paddy soil and limit cadmium accumulation in rice grains: A mechanistic investigation - Jiali Yan; Xuwei Li; Jintao Li; Jiankang Zhou; Jiamin Shi; Kangfu Liu; Xin Chen; Shiqi Zhou; Weiwei Sun; Fuqing Sui; Xiaochen Lin; Lei Zhang; et al. (Plant and Soil, 2025)

Selective ·OH generation in Fenton-like reaction by dual sulfur coordination of iron organic frameworks - Limin Duan; Huihao Jiang; Borui Cai; Jiali Wang; Wenhao Wu; Daohui Lin; Kun Yang (Water Research, 2025)

Red mud causes dynamic changes in the soil microbial community and cadmium fractions in a slightly cadmium-contaminated paddy soil - Jiali Yan; Xuwei Li; Zhengguo Pan; Xiaochen Lin; Qinglin Zuo; Jiankang Zhou; Shiqi Zhou; Fuqing Sui; Lei Zhang; Matthew H.H. Fischel (Journal of Hazardous Materials, 2025)

Detection of toluene at ppb levels using Au catalyst supported on Al-doped ZnO - Jiali Hong; Keyu Chen; Kaiping Yuan; Mingyue Lin; Qi Cao; Jialong Lin; XinLin Wang; Xiaoqian Bai; Tamao Ishida; Toru Murayama; Guangli Xiu (Journal of Environmental Chemical Engineering, 2025)

The formation of a hybrid fish derived from Labeo rohita ♀ × Cyprinus carpio ♂ and exhibiting stronger low temperature tolerance - Jiali Lin; Haoran Zhang; Jietao Wang; Bing Fu; Zexun Zhou; Wuhui Li; Huirong Yang; Shaojun Liu (Aquaculture, 2025)

Innovative immunosonogen nanoplatform combining sonodynamic oxygenation and immunomodulation for superior cancer therapy - Jiali Tang; Yanlu Chen; Hao Lai; Qi Zeng; Yu Li; Junqi Feng; Ningjing Lin; Ronghua Jin; Junjie Liu; Tao Luo; Zixuan Liang (Chemical Engineering Journal, 2025)

New insights into the effects of PFOS exposure on rat lung development: morphological, functional, and single-cell sequencing analysis - Jiali Mo; Jingye Zuo; Lin Yu; Huishan Zhang; Shuting Weng; Leping Ye (Archives of Toxicology, 2025)

Molecular and pharmacological characterization of the dopamine receptors in the oriental fruit fly, Bactrocera dorsalis - Shiyan Liu; Xuefeng Zhang; Xin Gong; Jinxin Yu; Tao Lin; Qian Xiang; Xinnian Zeng; Jiali Liu (Insect Biochemistry and Molecular Biology, 2025)

Engineering phosphorus vacancies in reduced graphene oxide anchored Co2P nanoparticles toward optimal supercapacitive properties - Jiali Zhong; Zhenyuan Ji; Xiang Gao; Zixin Lin; Xiaoyuan Lu; Guoxing Zhu; Keqiang Xu; Peng Song; Xiaoping Shen (Fuel, 2025)

Activation of persulfates on carbon nanotubes for water decontamination: Is the non-radical process consistently considered across different pH levels? - Jiali Peng; Lun Li; Shihuai Deng; Hongyu Zhou; Yanjun Li; Chenye Fu; Long Lin; Yue Yuan; Wei Wei; Guochun Lv; Gang Yang; Xiaohui Lu; et al. (Journal of Hazardous Materials, 2025)

Adding non-crop plants enhances parasitoid fitness on potato plants, but not pest densities - Yusha Wang; Yongping Zhou; Ruwen Li; Ambreen Masqsood; Hongsong Chen; Zhenqiang Qin; Jingfang Yang; Jiali Zhang; Lin Jing; Huihua Tan; Zhongshi Zhou (Crop Protection, 2025)

Construction of robust fluorescent probe for CO detection and assessment of the efficacy of hyperbaric oxygen therapy acute CO poisoning - Lin Yang; Liyi Zhou; Xiaomin Yuan; Lin Pengxu; Ting Liu; Lizao Chen; Jiali Ren (Journal of Hazardous Materials, 2025)

Dynamic multi-objective time-temperature management for climacteric fruit cold storage considering ripeness windows and energy consumption - Qian Chen; Jianping Qian; Huibin Li; Xintao Lin; Jiali Li; Zihan Liu; Zhiyao Zhao (Journal of Food Engineering, 2025)

Construction of diffusion and binding synergy in carbon-supported catalysts with varied Pd0/PdO Ratios for direct synthesis of hydrogen peroxide - Zhiheng Wang; Jiali Huang; Guancong Jiang; Tuo Ji; Han Lin; Liwen Mu; Xiaohua Lu; Jiahua Zhu (Chemical Engineering Journal, 2025)

Why Super Typhoon Occurrence Over the Western North Pacific Ocean Tends to be More in Autumn Than Summer - Zhiming Feng; Xiuping Yao; Chenfei Liao; Jiali Ma; Ning Pan; Yanluan Lin (International Journal of Climatology, 2025)
Based on the tropical cyclone (TC) best‐track datasets from the China Meteorological Administration during 1949–2020 and the fifth generation ECMWF atmospheric reanalysis (ERA5) datasets, we investigate the characteristics of super typhoons (SuperTYs) over the western North Pacific (WNP) and associated mechanism in this study. The results show that SuperTYs are prone to occur in autumn over the WNP, nearly 30% of the autumn TCs develop into SuperTYs, and autumn SuperTYs account for more than half of the annual total. This is due to both favourable oceanic and atmospheric conditions. In southeastern WNP, the sea surface temperature (SST) in autumn is higher than that in summer, inducing zonal circulation anomalies and enhancing low‐level westerlies. Consequently, the monsoon trough strengthens and extends eastward, favouring enhanced autumn typhoon occurrence in the southeastern WNP. This southeastward shift facilitates TCs to remain over the warm ocean for a longer period and makes them more prone to develop into SuperTYs. Furthermore, TCs tend to take westward‐moving tracks in autumn due to stronger easterly steering flows compared with summer, resulting in more TCs passing over the South China Sea (SCS) to the east of the Philippines where the vertical wind shear (VWS) is relatively weaker and prone to develop into superTYs.

The synergistic effect of pulsed red light and leonurus inhibits primary dysmenorrhea induced by oxytocin in mice by modulating calcium signaling and inhibiting inflammatory responses - Qiqi Fu; Hui Jiang; Jiali Yang; Haokuan Qin; Longfei Huo; Yi Ren; Shangfei Lin; Muqing Liu; Jinghui Yao (Journal of Photochemistry and Photobiology B: Biology, 2025)

New insights into uranium biomineralization mediated by Pseudomonas sp. WG2-6 in the presence of organic phosphorus: Promoting effect of extracellular polymeric substance and formation of U-P nanominerals - Lin Zhou; Siyu Hou; XingQi Duan; Yalin Lu; Jiali Liao; Ning Liu; Ran Zhao; Changsong Zhao (Journal of Hazardous Materials, 2024)

Asymmetric supercapacitors assembled by hollow N, s co-doped carbon spheres decorated FeOOH and Co3S4 nanoparticles - Zhenyuan Ji; Guanxiang Tang; Jingchuang Zhang; Xinghang Chuan; Jiali Zhong; Zixin Lin; Peng Song; Keqiang Xu; Xiaoping Shen (Chemical Engineering Journal, 2024)

Eu2+-activated hexagonal aluminate solid solution phosphors with high quantum efficiency and anti-thermal quenching for pc-LEDs - Yue Han; Mengfang Chen; Xiaochen Hu; Shuzhen Liao; Jiali Tang; Jiayuan Lin; Shixun Lian; Jilin Zhang (Chemical Engineering Journal, 2024)

Acid-assisted pretreatment for sweet elephant grass in choline chloride/glycerol DES: Experimental and mechanism study - Yining Zhang; Weizhen Xie; Weidong Li; Yue Tang; Jiali Wu; Lihui Gan; Ling-Ping Xiao; Xu Zhang; Lu Lin; Xing Tang (Chemical Engineering Journal, 2024)

Method development, multi-residue determination, and dietary exposure risk assessment of plant growth regulators in homologous materials of medicine and food - Wenqian Qiu; Jiali Chen; Yongyou Hua; Yan Yang; Shouer Lin (Environmental Monitoring and Assessment, 2024)

Catalytic combustion of light hydrocarbons over Pd − Pt/Al2O3: The hidden Pt1 active sites - Ziran Ma; Jiali Zhou; Jing Lin; Gongjin Yang; Shuang Liu; Ge Li (Fuel, 2024)

Inorganic Carbon Pools and Their Drivers in Grassland and Desert Soils - Longwei Dong; Jinzhi Ran; Jiali Luo; Lin Bai; Ying Sun; Muhammad Aqeel; Yahui Zhang; Xiaoting Wang; Qiajun Du; Junlan Xiong; Haiyang Gong; Qingqing Hou; et al. (Global Change Biology, 2024)
Inorganic carbon is an important component of soil carbon stocks, exerting a profound influence on climate change and ecosystem functioning. Drylands account for approximately 80% of the global soil inorganic carbon (SIC) pool within the top 200 cm. Despite its paramount importance, the components of SIC and their contributions to CO 2 fluxes have been largely overlooked, resulting in notable gaps in understanding its distribution, composition, and responses to environmental factors across ecosystems, especially in deserts and temperate grasslands. Utilizing a dataset of 6011 samples from 173 sites across 224 million hectares, the data revealed that deserts and grasslands in northwestern China contain 20 ± 2.5 and 5 ± 1.3 petagrams of SIC in the top 100 cm, representing 5.5 and 0.76 times the corresponding soil organic carbon stock, respectively. Pedogenic carbonates (PIC), formed by the dissolution and re‐precipitation of carbonates, dominated in grasslands, accounting for 60% of SIC with an area‐weighted density of 3.4 ± 0.4 kg C m −2 at 0–100 cm depth, while lithogenic carbonates (LIC), inherited from soil parent materials, prevailed in deserts, constituting 55% of SIC with an area‐weighted density of 7.1 ± 1.0 kg C m −2 . Soil parent materials and elevation determined the SIC stocks by regulating the formation and loss of LIC in deserts, whereas natural acidification, mainly induced by rhizosphere processes including cation uptake and H + release as well as precipitation, reduced SIC (mainly by PIC) in grasslands. Overall, the massive SIC pool underscores its irreplaceable role in maintaining the total carbon pool in drylands. This study sheds light on LIC and PIC and highlights the critical impact of natural acidification on SIC loss in grasslands.

Utilizing spontaneous plants for sustainable development in residential green spaces: Insights from environmental drivers and niche analysis in Fuzhou City, China - Chengyu Ran; Junyi Pan; Yuxin Lin; Tongyan Li; Yaling Huang; Jingkai Huang; Shiyuan Fan; Wenqiang Fang; Shuang Zhao; Yuxiang Liu; Jiali Jin; Weicong Fu (Journal of Environmental Management, 2024)

Golden-flower fungus (Eurotiwm Cristatum) presents fungal flower aroma as well as accelerates the aging of white tea (Shoumei) - Wan Zhu; Su Zhou; Haowei Guo; Jiali Hu; Yanyan Cao; Yingxin Xu; Xingchen Lin; Baoming Tian; Fangyuan Fan; Shuying Gong; Ping Chen; Qiang Chu (Food Chemistry, 2024)

Multiscale coupling analysis and modeling of airflow and heat transfer for warehouse-packaging-kiwifruit under forced-air cooling - Qian Chen; Jianping Qian; Han Yang; Jiali Li; Xintao Lin; Baogang Wang (Biosystems Engineering, 2024)

Challenges and enhancement technologies of medium chain carboxylates production in open culture anaerobic fermentation - Shu-Lin Wu; Lan Wu; Wei Wei; Jiali Shentu; Yuyang Long; Dongsheng Shen; Bing-Jie Ni (Chemical Engineering Journal, 2024)

Novel tri-solvent amines absorption for flue gas CO2 capture: Efficient absorption and regeneration with low energy consumption - Guanghuan Li; Xuehua Shen; Xianfeng Jiao; Feng Xie; Jiali Hua; Han Lin; Feng Yan; Hao Wu; Zuotai Zhang (Chemical Engineering Journal, 2024)

Awakening dumb Mn2+ mechanoluminescence site to achieve force, temperature and time-domain induced color tuning via trap-assisted energy transfer - Jiaqi Ou; Shuangqiang Fang; Haoliang Cheng; Dongjie Han; Qiangqiang Zhu; Yue Zhai; He Lin; Jiali Yu; Renjie Xu; RongJun Xie; Le Wang (Chemical Engineering Journal, 2024)

Against catalyst deactivation during toluene oxidation on CuCeOx in flue gas: High oxidation efficiency and rapid oxidation pathway - Ziyang Guo; Beilong Lin; Jiali Tang; Jinhang Yang; Lan Fan; Mingli Fu; Daiqi Ye; Yun Hu (Journal of Environmental Chemical Engineering, 2024)

In-depth impact evaluation of binders on the mechanical properties and CO2 capture performance of CaO-based particles - Xuehua Shen; Ruiheng Zhang; Yiping Su; Han Lin; Feng Xie; Yingying Cai; Guanghuan Li; Jiali Hua; Feng Yan; Zewei Quan; Zuotai Zhang (Journal of Environmental Chemical Engineering, 2024)

An Efficient Vector-Based CRISPR/Cas9 System in Zebrafish Cell Line - Xiaokang Ye; Jiali Lin; Qiuji Chen; Jiehuan Lv; Chunsheng Liu; Yuping Wang; Shuqi Wang; Xiaobo Wen; Fan Lin (Marine Biotechnology, 2024)

Phosphorothioate-modified G-quadruplex as a signal-on dual-mode reporter for CRISPR/Cas12a-based portable detection of environmental pollutants - Kai Shi; Yi Tian; Sujun Liu; Wenjie Luo; Keer Liu; Lin Zhang; Ying Zhang; Jiali Chang; Jiaheng Zhang; Shuo Wang (Analytica Chimica Acta, 2024)

PIM-1-based membranes mediated with CO2-philic MXene nanosheets for superior CO2/N2 separation - Kaifang Wang; Danlin Chen; Jiali Tang; Zihao Hong; Zhongtai Zhu; Ziyi Yuan; Zhihong Lin; Yuqi Liu; Raphael Semiat; Xuezhong He (Chemical Engineering Journal, 2024)

Attribution analysis of non-stationary hydrological drought using the GAMLSS framework and an improved SWAT model - Youxin Wang; Tao Peng; Yanhu He; Vijay P. Singh; Qingxia Lin; Xiaohua Dong; Tianyi Fan; Ji Liu; Jiali Guo; Gaoxu Wang (Journal of Hydrology, 2023)

Mitochondria-related lncRNAs: predicting prognosis, tumor microenvironment and treatment response in lung adenocarcinoma - Qianhui Zhou; Jiali Xiong; Yan Gao; Rong Yi; Yuzhu Xu; Quefei Chen; Lin Wang; Ying Chen (Functional & Integrative Genomics, 2023)
Lung cancer is the most common type of malignant tumor that affects people in China and even across the globe, as it exhibits the highest rates of morbidity and mortality. Lung adenocarcinoma (LUAD) is a type of lung cancer with a very high incidence. The purpose of this study was to identify potential biomarkers that could be used to forecast the prognosis and improve the existing therapy options for treating LUAD. Clinical and RNA sequencing data of LUAD patients were retrieved from the TCGA database, while the mitochondria-associated gene sets were acquired from the MITOMAP database. Thereafter, Pearson correlation analysis was carried out to screen mitochondria-associated lncRNAs. Furthermore, univariate Cox and Lasso regression analyses were used for the initial screening of the target lncRNAs for prognostic lncRNAs before they could be incorporated into a multivariate Cox Hazard ratio model. Then, the clinical data, concordance index, Kaplan–Meier (K-M) curves, and the clinically-relevant subjects that were approved by the Characteristic Curves (ROC) were employed for assessing the model's predictive value. Additionally, the differences in immune-related functions and biological pathway enrichment between high- and low-risk LUAD groups were examined. Nomograms were developed to anticipate the OS rates of the patients within 1-, 3-, and 5 years, and the differences in drug sensitivity and immunological checkpoints were compared. In this study, 2175 mitochondria-associated lncRNAs were screened. Univariate, multivariate, and Lasso Cox regression analyses were carried out to select 13 lncRNAs with an independent prognostic significance, and a prognostic model was developed. The OS analysis of the established prognostic prediction model revealed significant variations between the high- and low-risk patients. The AUC-ROC values after 1, 3, and 5 years were seen to be 0.746, 0.692, and 0.726, respectively. The results suggested that the prognostic model riskscore could be used as an independent prognostic factor that differed from the other clinical characteristics. After analyzing the findings of the study, it was noted that both the risk groups showed significant differences in their immune functioning, immunological checkpoint genes, and drug sensitivity. The prognosis of patients with LUAD could be accurately and independently predicted using a risk prediction model that included 13 mitochondria-associated lncRNAs.

Expression analysis, clinical significance and potential function of PLXNB2 in acute myeloid leukaemia - Zhibo Guo; Dan Guo; Desheng Kong; Sicheng Bian; Linlin Zhao; Qi Li; Leilei Lin; Jiali Hao; Lili Sun; Yinghua Li (Molecular Biology Reports, 2023)

Genome-Wide Analysis of Family I84 Protease Inhibitor Genes in Three Bivalves Reveals Important Information About the Protein Family’s Evolution - Jinxia Mao; Jiali Lu; Sheng Liu; Youli Liu; Zhihua Lin; Qinggang Xue (Marine Biotechnology, 2023)

Spatial differences, dynamic evolution, and convergence of carbon productivity in China - Jiali Kou; Xiaoguang Xu; Weizhao Lin; Huan Wang (Environmental Science and Pollution Research, 2023)

Oxidative Stress in Diabetic Peripheral Neuropathy: Pathway and Mechanism-Based Treatment - Qingxia Lin; Kezheng Li; Yinuo Chen; Jiali Xie; Chunxue Wu; Can Cui; Binbin Deng (Molecular Neurobiology, 2023)

Cadmium and lead removal by Mg/Fe bimetallic oxide-loaded sludge-derived biochar: batch adsorption, kinetics, and mechanism - Weixiong Lin; Jiali Zhou; Shuiyu Sun (Environmental Science and Pollution Research, 2023)

Radiation synthesis of rapidly self-healing, durable, and flexible poly(ionic liquid)/MXene gels with anti-freezing property for multi-functional strain sensors - Wenchao Zhao; Jiali Jiang; Wentao Chen; Yuqi He; Tingrui Lin; Long Zhao (Chemical Engineering Journal, 2023)

Differences in the diversity and community structure of the intestinal microbiota of commercial fishes in the central and southern East China Sea in spring and autumn - Jiali Xiang; Shigang Liu; Puqing Song; Ran Zhang; Yuan Li; Longshan Lin (Environmental Biology of Fishes, 2023)

Multi-trait analysis reveals large interspecific differences for phytoplankton in response to thermal change - Mengcheng Ye; Mengting Xiao; Shufei Zhang; Jiali Huang; Jiamin Lin; Yucong Lu; Shiman Liang; Jingyuan Zhao; Xiaoying Dai; Leyao Xu; Mingke Li; Yunyue Zhou; et al. (Marine Environmental Research, 2023)

Long-term exposure to ambient air pollutants and their interaction with physical activity on insomnia: A prospective cohort study - Yijuan Lin; Yinyan Gao; Xuemei Sun; Jiali Wang; Shuzi Ye; Irene X.Y. Wu; Fang Xiao (Environmental Research, 2023)

Long-term adaptation to elevated temperature but not CO2 alleviates the negative effects of ultraviolet-B radiation in a marine diatom - Peng Jin; Jiaofeng Wan; Xiaoying Dai; Yunyue Zhou; Jiali Huang; Jiamin Lin; Yucong Lu; Shiman Liang; Mengting Xiao; Jingyuan Zhao; Leyao Xu; Mingke Li; et al. (Marine Environmental Research, 2023)

Experimental and kinetic model evaluation of HONO production from surface nitrate photolysis - Youfeng Wang; Jianshu Wang; Yaru Wang; Yingjie Zhang; Robert Woodward-Massey; Chong Zhang; Yu Kuang; Jiali Zhu; Jing Shang; Xin Li; Limin Zeng; Weili Lin; et al. (Atmospheric Environment, 2023)

Genetic diversity monitoring of Chiloscyllium plagiosum from coastal Xiamen between generations - Liyan Zhang; Shigang Liu; Zizi Cai; Jiali Xiang; Puqing Song; Yueping Zhang; Yuan Li; Longshan Lin (Regional Studies in Marine Science, 2023)

Propagation from meteorological to hydrological drought and its application to drought prediction in the Xijiang River basin, South China - Qingxia Lin; Zhiyong Wu; Yuliang Zhang; Tao Peng; Wenjuan Chang; Jiali Guo (Journal of Hydrology, 2023)

Diet Influences the Gut Microbial Diversity and Olfactory Preference of the German Cockroach Blattella germanica - Jian Zhu; Yinghua Wu; Fei Lin; Guodong Liao; Jiali Wang; Jiaqi Wei; Hanhong Xu (Current Microbiology, 2023)

A Novel Preparation Method for Effervescent Tablets of Xianganfang Containing Fresh Juice using a Semi-Solid Extrusion 3D Printer with Three Cartridge Holders - Xiangru Dong; Wenfang Zhang; Xiaoting Wang; Sijia Liu; Jiawei Liang; Chunqiao Liufu; Shaofeng Zeng; Jiali Pang; Siting Li; Lingjuan Xiong; Guoyan Zhou; Weixing Zhu; et al. (AAPS PharmSciTech, 2022)

Differentiation and Temperature Adaptation of Pampus Echinogaster Based on Genome-Wide SNPs - Yuan Li; Fangrui Lou; Shigang Liu; Hai Li; Jiali Xiang; Binbin Shan; Longshan Lin; Xuan Zhuang (Frontiers in Marine Science, 2022)
Climate change and overfishing have led to the degradation of the quality and stock of Pampus echinogaster. Exploring the genetic structure and local adaptive evolutionary mechanisms of P. echinogaster is crucial for the management of this species. This population genomic study of nine geographical populations of P. echinogaster in China was conducted by specific-locus amplified fragment sequencing (SLAF-seq). A total of 935,215 SLAF tags were obtained, and the average sequencing depth of the SLAF tags was 20.80×. After filtering, a total of 46,187 high-consistency genome-wide single nucleotide polymorphisms (SNPs) were detected. Based on all SNPs, the population size of the nine P. echinogaster geographical populations was large. The Shantou population had the lowest genetic diversity, and the Tianjin population had the highest. Moreover, the population genetic structure based on all SNPs revealed significant gene exchange and no significant genetic differentiation among the nine P. echinogaster geographical populations, probably because of the population expansion after the last glacial period, the lack of balance between migration and genetic drift, and the long-distance diffusion of eggs and larvae. We suspect that variation of material metabolism, ion transfer, breeding, stress response, and inflammatory reactions-related genes were critical for adaptation to spatially heterogeneous temperature selection in natural P. echinogaster populations.

Characteristics of Ichthyoplankton Communities and Their Relationship With Environmental Factors Above the Ninety East Ridge, Eastern Indian Ocean - Liyan Zhang; Jing Zhang; Shigang Liu; Rui Wang; Jiali Xiang; Xing Miao; Ran Zhang; Puqing Song; Longshan Lin (Frontiers in Marine Science, 2021)
The Ninety East Ridge is a submarine north–south oriented volcanic ridge in the eastern Indian Ocean. Surface-layer ichthyoplankton collected in this area from September to October were identified by combined morphological and molecular (DNA barcoding) techniques, and their species composition, diversity, and abundance, and correlations with environmental variables were described. Collections comprised 109 larvae and 507 eggs, which were identified to 37 taxa in 7 orders, 20 families, and 27 genera, and were dominated by the order Perciformes and species Vinciguerria sp., Oxyporhamphus micropterus , and Decapterus macarellus . Species abundances at each station and of each species were relatively low, suggesting that this area or the time of sampling were not of major importance for fish spawning. Waters above Ninety East Ridge had lower species diversity but higher species richness than waters further offshore. A generalized additive model revealed that high abundance of ichthyoplanktonic taxa occurred in areas with low sea surface height and high sea surface salinity, temperature, and chlorophyll a concentration. Of these, sea surface height was most correlated with ichthyoplankton abundance. We provided baseline data on surface-dwelling ichthyoplankton communities in this area to aid in development of pelagic fishery resources in waters around the Ninety East Ridge.

Mortality burden caused by diurnal temperature range: a nationwide time-series study in 364 Chinese locations - Min Cai; Jianxiong Hu; Chunliang Zhou; Zhulin Hou; Yanjun Xu; Maigeng Zhou; Yize Xiao; Biao Huang; Xiaojun Xu; Lifeng Lin; Tao Liu; Jianpeng Xiao; et al. (Stochastic Environmental Research and Risk Assessment, 2021)

Identification and Sexually Dimorphic Expression of a FoxL2-like Gene in Mud Crab (Scylla paramamosain): Potential Roles in Male Differentiation and Development - Yuying Yuan; Jiali Lin; Xueying Tan; Xi Shi; Shaobin Fang; Yin Zhang; Hongyu Ma; Fan Lin (Thalassas: An International Journal of Marine Sciences, 2021)

The undrained vertical and horizontal bearing capacity of internal skirted foundation in clay - Chong Jiang; Liu Lin; Chen Li; Tian-Bin Li; Jiali He (European Journal of Environmental and Civil Engineering, 2020)

Identification of a novel bocaparvovirus in a wild squirrel in Kunming, Yunnan Province, China - Jiali Wang; Nan Li; Zhao Li; Lin Liu; Yuwen He; Jinxin Meng; Shunxiang Li; Jinglin Wang (Archives of Virology, 2020)

Plant growth regulators affect biomass, protein, carotenoid, and lipid production in Botryococcus braunii - Huanmin Du; Jiali Ren; Zhe Li; Haonan Zhang; Kang Wang; Bin Lin; Shanmin Zheng; Changyu Zhao; Chunxiao Meng; Zhengquan Gao (Aquaculture International, 2020)

Molecular cloning, characterization and expression profiles of a SoxB2 gene related to gonadal development in mud crab ( Scylla paramamosain ) - Jiali Lin; Yuying Yuan; Xi Shi; Shaobin Fang; Yin Zhang; Mengyun Guan; Zhuofang Xie; Hongyu Ma; Fan Lin (Invertebrate Reproduction & Development, 2020)

Salinity mediates the effects of nitrogen enrichment on the growth, photosynthesis, and biochemical composition of Ulva prolifera - Mingshan Zheng; Jiajia Lin; Shidan Zhou; Jiali Zhong; Yahe Li; Nianjun Xu (Environmental Science and Pollution Research, 2019)

The abuse of anesthetic propofol: associated with cognitive impairment - Weili Zhu; Wen Zhang; Jiali Li; Zengbo Ding; Yingjie Huang; Lin Lu (Science China Life Sciences, 2018)

Agrobacterium-mediated transformation of centipedegrass (Eremochloa ophiuroides [Munro] Hack.) - Mingxi Liu; Shaoyun Lu; Lin Liu; Jiali Tan; Zhenfei Guo (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

ASIP genetic variants and the number of non-melanoma skin cancers - Wen Lin; Abrar A. Qureshi; Peter Kraft; Hongmei Nan; Qun Guo; Frank B. Hu; Majken K. Jensen; Jiali Han (Cancer Causes & Control, 2011)

Inhibition of NFkappaB by activated c-Jun NH2 terminal kinase 1 acts as a switch for C2C12 cell death under excessive stretch - Jiali Tan; Wei Kuang; Zuolin Jin; Fang Jin; Lin Xu; Qiujun Yu; Liang Kong; Guang Zeng; Xiao Yuan; Yinzhong Duan (Apoptosis, 2009)

Novel mutations in the IRF6 gene for Van der Woude syndrome - Xiaofang Wang; Jiali Liu; Haibing Zhang; Mingzhen Xiao; Jinfeng Li; Chunling Yang; Xianjun Lin; Zizhong Wu; Landian Hu; Xiangyin Kong (Human Genetics, 2003)